Preparation and characterization of PEGylated C18 fatty acids/Anti-SNAP25 antibody-targeted Liposomes - Gew, Lai Ti *; Eh, Suk Vicit Rizal; Misni Misran, Prof Dr (Bentham Science, 2019)
Background: Unsaturated C18 fatty acids, such as oleic acid (L1), linoleic acid (L2), and linolenic acid (L3), are a good choice of lipids to prepare liposomes. They are inexpensive, biocompatible, nontoxic, and readily available compared with phospholipids. Moreover, cis-double bonds of unsaturated fatty acids prevent the packing of molecules which increases membrane fluidity in liposomes making them a good choice of starting materials to prepare liposomes. Objective: Unsaturated C18 fatty acid liposomes, as well as their PEGylated and nonPEGylated antibody-targeted liposomes, were prepared and characterized. Method: The particle size and zeta potential of the prepared liposomes (1 mM, pH = 7.4) for 28 and 14 days, respectively, were monitored and characterized. Membrane-bound antibodies Anti-SNAP25 (AS25) and DOPE PEG2000 (DP) were conjugated to pure C18 fatty acid liposomes to achieve stable fatty acid formulations. Results: The mean particle sizes of pure L1, L2, and L3 liposome solutions were 125, 129, and 122 nm respectively, while their polydispersity index values were 0.28, 0.21, and 0.40 respectively. A large negative zeta potential value of 45 mV was observed due to anionic carboxylate head-group of pure liposomes. The incorporation of AS25 into L1/DP, L2/DP, and L3/DP liposome solutions stabilized their mean particle size and zeta potential measurements over 28 and 14 days, respectively. Conclusion: L1/DP/AS25 was found to be the most stable PEGylated antibody-targeted liposome system because its particle size remained between 90 and 125 nm in 28 days. Transmission electron microscopy observations also supported the incorporation of AS25 and DP on the membrane surface as predicted.